Integration of Soeharto's Leadership Values in History Lessons on Indonesia's New Order Era in Three Senior High Schools in Cirebon, West Java - Della Nur Fauziah Syadiyah (Indonesian Journal of History Education, 2024)
This research aims to analyse the implementation of history teaching in three senior high schools (SMAN) in Cirebon City, focusing on Indonesia during the New Order era in Grade XII. It also examines the learning resources used by history teachers and how students internalize Soeharto’s leadership values during lessons. A qualitative method with a descriptive approach was employed, with data collected through interviews, observations, and document studies. Data validity was ensured through technique and source triangulation, while data analysis followed the stages of data reduction, presentation, and conclusion drawing. The findings reveal that: (1) History lessons were conducted according to the 2013 curriculum, using lesson plans (RPP) developed through MGMP discussions and history textbooks. Teachers used lectures and discussions, supported by visual and audio-visual media to teach Soeharto's leadership values; (2) The primary learning resources included school-provided history textbooks and supplementary materials from teacher’s guidebooks; (3) Students successfully internalized Soeharto’s leadership values, such as responsibility, hard work, patriotism, and discipline, and applied these values in their daily lives. This research offers significant insights into the effectiveness of history teaching in shaping students' character through the internalization of historical values.